Development of an ethnobiology supplement book based on the study of medicinal plants in Wonawa District, Kepulauan Yapen Serui Regency - Horota, Serlin; Damopolii, Insar; Kilmaskossu, Johanis Paulus; Nusantari, Elya (Inornatus: Biology Education Journal, 2023)
This study aims to produce a supplement book for ethnobiology courses based on research on traditional medicinal plants in Wonawa District, Kepulauan Yapen Serui Regency. The type of research is research and development. The ADD (analysis, design, and development) stage of the ADDIE model is applied to the development of supplement books. Interviews are used for data collection and identification of medicinal plants. Experts validate books made while students fill out response questionnaires. The validity criteria for supplement books with a value of 88.63% based on the findings of the research are Very Valid. In the Excellent category are responses to supplement booksÂ from students with an average rate of 87.5%. The developed supplement book can be used for student learning because it fulfills the valid criteria and the response has been overwhelmingly positive.